The Reverse of the Curse Paul, Wisdom, and the Law - Pate, C Marvin (Mohr Siebeck, 2000)
Die Umkehrung des Fluches. Paulus, die Weisheit und das Gesetz. Von C. Marvin Pate.
PublicationDate: 20191210
Keywords: Paulus (Apostel) -- Neues Testament -- Array